2017
DOI: 10.1177/1010428317698382
|View full text |Cite
|
Sign up to set email alerts
|

Tumor protein D52 (isoform 3) contributes to prostate cancer cell growth via targeting nuclear factor-κB transactivation in LNCaP cells

Abstract: Our previous study showed that TPD52 overexpression could increase migration and proliferation of LNCaP cells contributing to the development of prostate cancer. However, mechanism of TPD52 in prostate cancer initiation and progression remains elusive. In this study, we investigated the possible underlying mechanism of TPD52 in prostate cancer progression. In LNCaP cells, TPD52 expression was altered by transfecting with either EGFP-TPD52 or specific short hairpin RNA. Overexpression of TPD52 protected LNCaP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Tumor protein D52 (TPD52), a chromosome 8q21 amplification target, acts as an oncogene in many cancers, including PCa. 25,26 Coincidently, by bioinformatics analysis, we found that both circ-XIAP and 3ʹUTR of TPD52 had the complementary binding sequence for miR-1182, which suggested the interactions among circ-XIAP, miR-1182 and TPD52 in DTX resistance of PCa.…”
Section: Introductionmentioning
confidence: 69%
“…Tumor protein D52 (TPD52), a chromosome 8q21 amplification target, acts as an oncogene in many cancers, including PCa. 25,26 Coincidently, by bioinformatics analysis, we found that both circ-XIAP and 3ʹUTR of TPD52 had the complementary binding sequence for miR-1182, which suggested the interactions among circ-XIAP, miR-1182 and TPD52 in DTX resistance of PCa.…”
Section: Introductionmentioning
confidence: 69%
“…In addition, overexpression of miR-379 reduced TPD52 mRNA and protein expression levels, suggesting that miR-379 negatively regulated the TPD52 protein synthesis though degradation of the mRNA. Recently, a previous study revealed that elevated TPD52 levels may promote the migration and proliferation of prostate cancer LNCaP cells though activation of nuclear factor-κB signaling ( 34 ). Consistently, the present study observed that the knockdown of TPD52 was able to inhibit the growth, migration and invasion of NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, all members have been found to be overexpressed in a series of cancers (Cao et al, 2006;Byrne et al, 1995Byrne et al, , 1998Nourse et al, 1998). Overexpression of TPD52 correlates with poor prognosis in breast cancer patients, and in cell models, TPD52 overexpression promotes proliferation and invasion (Byrne et al, 2010(Byrne et al, , 1996Li et al, 2017;Dasari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%